Different experiments for the production of charcoal with green coconut shells - Gama, Lucas; Ströher, Gylles Ricardo; Ströher, Gisely Luzia (Seven Editora, 2023)
OBJECTIVE: To produce charcoal from green coconut shells. METHODS: The green coconut shells were collected from vendors in the city, sanitized, opened and placed outdoors to reduce humidity. 8 different experiments were carried out at varying temperatures (300 and 450ºC), time (1 and 2 h), and mass (35 and 100 g) to obtain the best product yield. The data were submitted to Tukey's new test, p<0.05. RESULTS: The best yield was obtained at a temperature of 300ºC, for 2 h in 100 g of coconut shell samples producing 54.81 ± 2.29 g of charcoal, that is, a yield of 53.80 ± 0.89%, with volatile moisture content equal to 6.97 ± 1.71 % and 6.50 ± 2.50 % of ash. CONCLUSIONS: The smaller amounts of ash, as well as moisture and volatiles, are more interesting because they reduce soot and the inefficiency of the burning process. Coals produced from the shell of green coconut can be one of the sustainable solutions to the Brazilian energy crisis. DOI:https://doi.org/10.56238/alookdevelopv1-056